Pemanfaatan Konten Ibadah dan Akhlak dalam Media Sosial - Jefri Adiguna; Zainal Fadri; Irman Irman (Istinarah: Riset Keagamaan, Sosial dan Budaya, 2020)
This study aims to determine the use of religious content and morals in social media for adolescents. The method used is descriptive qualitative, where adolescents are respondents, the technique of collecting data is interviewing and observing the data analysis using a technique developed by Miles and Huberman, and testing the validity of the data through triangulation. The results of the study found, (1) religious content and morals on social media Facebook, Instagram, and WhatsApp have been utilized by teenagers, (2) social media that teenagers often use, namely Facebook, Instagram, WhatsApp and YouTube, teenagers often see and share. videos and posting of religious and moral content, (3) worship and morals content on social media are used through discussions among members of the mosque's youth regarding its benefits and applications.